RANCANG BANGUN INTERKONEKSI RANGKAIAN BERBASIS CROSSBAR SWITCH DAN APLIKASI WEB - Taqiy Asyam Listyawan; Waru Djuriatno; Raden Arief Setyawan (Jurnal Mahasiswa TEUB, 2023)
Breadboards are often used in electronics prototyping which have a construction with several IO pins that each pin has several interconnected points to IO. To connect these pins, jumper cables are used at the pin points are connected. The construction is similar to the crossbar switch. Crossbar switches have two lines, namely horizontal and vertical with a relay at each intersection.The construction can be used as a circuit interconnect programmatically through a web application. In this design, the design is divided into five parts, including: crossbar switch module design, control module, disconnect function and connect function. The result of this design is the vertical crossbar switch lines are used as IO pins while the horizontal lines are used as line like a jumper cable. BL155 is used for relay. In this test, the relay resistance between IO and the line around 0.2Ohm – 0.3Ohm. The voltage drop on the relay is not found. Application test shows that the application is able to make the steps of disconnection, connection, and changing the address on the application to the address on the device. Keywords : Breadboard, Crossbar Switch, Web Application, Electronic Prototyping, BL1555 DAFTAR PUSTAKAFaudin, A. (2017, Juli 24). Memahami dengan mudah apa itu breadboard atau project board. Diambil kembali dari Nyebarilmu.com: https://www.nyebarilmu.com/memahami-dengan-mudah-apa-itu-breadboardatau-project-board/Freeman, R. L. (2004). Telecommunication System Engineering, Fourth Edition. New Jersey: Wiley.Wijayanti, N. N. (2021, Januari 2021). Website vs Web Application : Pilih yang Mana Ya? Diambil kembali dari Niaga Hoster:https://www.niagahoster.co.id/blog/web site-vs-web-app/Switch Analog